2015
DOI: 10.1007/s12022-015-9379-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Ki-67 Index Quantification Methods and Clinical Significance in Pancreatic Neuroendocrine Tumors

Abstract: The Ki-67 index is essential in the pathological reports for pancreatic neuroendocrine tumors. There are three methods to determine the Ki-67 index including eyeball estimation, manual counting, or automated digital imaging analysis. The goal of this study was to compare the three quantification methods with the clinical outcome to determine the best method for clinical practice. Ki-67 immunostaining was performed on 97 resected pancreatic neuroendocrine tumors. The three methods of quantification were employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 34 publications
1
29
0
1
Order By: Relevance
“…However, multi-institutional studies showed that formal counting was more reproducible than estimation in breast cancer [53,75]. Similar observation were made in NEN: results of eyeballed estimation differed from results of counting [20,21,25] and were irreproducible [25], but some investigators showed that estimation was not as bad [27,28]. Pathologists in general overestimate the Ki67 LI during eye-balled estimation in comparison to counting technique [25,27].…”
Section: Toward Optimal Methods Of Ki67 LI Assessmentmentioning
confidence: 52%
See 1 more Smart Citation
“…However, multi-institutional studies showed that formal counting was more reproducible than estimation in breast cancer [53,75]. Similar observation were made in NEN: results of eyeballed estimation differed from results of counting [20,21,25] and were irreproducible [25], but some investigators showed that estimation was not as bad [27,28]. Pathologists in general overestimate the Ki67 LI during eye-balled estimation in comparison to counting technique [25,27].…”
Section: Toward Optimal Methods Of Ki67 LI Assessmentmentioning
confidence: 52%
“…Analytical validity is a sine qua non condition for any tumour biomarker which is intended to be used in clinical practice and to influence management of the patients [18]. Selected aspects of analytical validity of Ki67 LI in NEN were previously studied [19,20,21,22,23,24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…These measures likely minimized the impact of inter‐ and intraobserver variability in Ki‐67staining quantification. In addition, the most reliable, albeit time‐consuming manual counting technique for Ki‐67 was used in this study . These above points are major strengths of our study.…”
Section: Discussionmentioning
confidence: 97%
“…Emphasizing the importance of this, Adsay noted, “In our experience, almost half of the cases are placed in a different World Health Organization grade on the basis of the area chosen for counting.” (22) In our study, interobserver agreement for Ki67-only stained slides was similar to that seen by Reid et al (21) using their “manual eye count” – a method equivalent to that used in the current study. It is also worthwhile noting that a subset of studies focuses solely on pancreatic neuroendocrine tumors (8, 21, 26) – which are morphologically more homogeneous with few peri-tumoral stromal lymphocytes or entrapped non-neoplastic glands. Thus, these studies may not capture the intricacies related to assessing Ki67 proliferative index of gastrointestinal neuroendocrine tumors in general.…”
Section: Discussionmentioning
confidence: 99%